2017
DOI: 10.2139/ssrn.2958098
|View full text |Cite
|
Sign up to set email alerts
|

The Southern African Poultry Value Chain: Regional Development Versus National Imperatives

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Value chain analysis work done to date in southern Africa (such as that on the southern African poultry value chain; see Ncube et al 2017) has identified as one of the two most important barriers to increased regional trade narrowly defined domestic policies that protect domestic economic interests and undermine the development of integrated regional value chains. Although there is an apparent general high-level policy consensus that the growth of such value chains is an important long-term strategy in the economic development of the region, non-tariff trade barriers (NTBs) appear to be increasing, in particular the use of local content regulations (LCRs).…”
Section: Introductionmentioning
confidence: 99%
“…Value chain analysis work done to date in southern Africa (such as that on the southern African poultry value chain; see Ncube et al 2017) has identified as one of the two most important barriers to increased regional trade narrowly defined domestic policies that protect domestic economic interests and undermine the development of integrated regional value chains. Although there is an apparent general high-level policy consensus that the growth of such value chains is an important long-term strategy in the economic development of the region, non-tariff trade barriers (NTBs) appear to be increasing, in particular the use of local content regulations (LCRs).…”
Section: Introductionmentioning
confidence: 99%